2006
DOI: 10.1369/jhc.5a6881.2006
|View full text |Cite
|
Sign up to set email alerts
|

Altered Expression of Ezrin in Esophageal Squamous Cell Carcinoma

Abstract: Ezrin is a membrane-cytoskeletal linker belonging to the ezrin-radixin-moesin (ERM) family and has been suggested to be involved in tumorigenesis. In this study we investigated ezrin expression pattern in normal esophageal mucosa and esophageal squamous cell carcinoma (ESCC) and the correlation with clinical characteristics. Immunohistochemical staining showed a tendency for ezrin to translocate from membrane to cytoplasm in the progression from normal epithelium to invasive carcinoma of the esophagus. By West… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 28 publications
(42 reference statements)
4
40
0
Order By: Relevance
“…Survival-Our recent study on ESCC samples showed that ezrin tends to translocate from the plasma membrane to the cytoplasm in the progression from normal epithelium to invasive carcinoma of the esophagus (16). Here, we confirmed this finding and further evaluated clinical significance.…”
Section: Ezrin Overexpression In Esccs Is Associated With Poorsupporting
confidence: 80%
See 1 more Smart Citation
“…Survival-Our recent study on ESCC samples showed that ezrin tends to translocate from the plasma membrane to the cytoplasm in the progression from normal epithelium to invasive carcinoma of the esophagus (16). Here, we confirmed this finding and further evaluated clinical significance.…”
Section: Ezrin Overexpression In Esccs Is Associated With Poorsupporting
confidence: 80%
“…We also have demonstrated that ezrin is overexpressed in a malignantly transformed esophageal epithelial cell line compared with an immortalized cell line (15). Our more recent study on esophageal squamous cell carcinoma (ESCC) 3 samples showed that ezrin tends to translocate from the plasma membrane to the cytoplasm in the progression from normal epithelium to invasive carcinoma of the esophagus (16). Moreover, both in vivo and in vitro experiments suggest that ezrin may affect tumor formation and tumor invasiveness directly (17).…”
mentioning
confidence: 99%
“…Western blotting was performed according to standard methods as described previously (18,19). Briefly, ESCC tissues and normal esophageal tissues were lysed in a sample buffer (50 mM Tris-HCl, pH 8.0; 150 mM NaCl, 1% Triton X-100; 100 μg/ml PMSF) on ice for 30 min.…”
Section: In Situ Hybridization (Ish)mentioning
confidence: 99%
“…Previous research indicates Ezrin plays critical roles in the invasion and metastasis of ESCC [8][9][10]. In this study, we present a comprehensive analysis of mRNA profile following Ezrin knockdown in ESCC EC109 cell line by using various bioinformatic methods to reveal the potential mechanisms of Ezrin action.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous researches show Ezrin is over-expressed in human esophageal squamous cell carcinoma (ESCC), which is associated with the invasive phenotype of malignantly transformed esophageal epithelial cells [8]. We subsequently found Ezrin translocates from the plasma membrane to the cytoplasm in the progression from normal epithelium to invasive carcinoma of esophageal epithelial cells [9].…”
Section: Introductionmentioning
confidence: 96%